Effect of Delayed Examination of the Morning Urine Sample After 3 Hours at Room Temperature - Eka Nurdianty Anwar; Ahmad Jais (ANJANI Journal (Medical Science & Healthcare Studies), 2021)
Intoduction: The study entitled The effect of delaying the examination of morning urine samples after 3 hours at room temperature to determine the effect of delaying the examination of morning urine samples after 3 hours at room temperature on urine sediment examination. Method: This study used 30 samples from the population of the Harapan Bangsa Health Analyst Academy students by random sampling..Result and Discussion: The study using the percentage formula obtained the following results: positive erythrocyte examination (1) fresh urine 77%, 3 hour urine 87%, positive (2) fresh urine 20%, 3 hour urine 13%, positive (3) fresh urine3% , urine 3 hours 0%. Leukocyte examination positive (1) fresh urine 47%, urine 3 hours 87% positive (2) fresh urine 47%, urine 3 hours 13%, positive (3) fresh urine 6%, urine 3 hours 0%. Bacterial examination, positive morning urine 23% negative 77%, 3-hour urine positive 100%. Urine examination is very important, especially in establishing a diagnosis of urinary tract infection (UTI). Conclusion: Delay in examination results in errors in diagnosis.